Challenging Diagnosis of Severe Bilateral Cervicofacial Subcutaneous Emphysema following Root Perforation in a Maxillary Lateral Incisor: A Case Report - Khoshkhounejad, Mehrfam; Hashemi Nasab, Mahboube Sadat; Aminsobhani, Mohsen; Moayeri, Razieh Sadat (Iranian Endodontic Journal, 2019)
Cervicofacial subcutaneous emphysema (CFSE) is a rare complication. CFSE may happen following some dental procedures including root canal therapy and is caused by unintentional entry of air into potential spaces of head and neck. In the current report, a case of extensive bilateral subcutaneous emphysema -following the root perforation of a maxillary anterior tooth- is presented. A 26-year-old woman was referred for further consultation concerning her right maxillary lateral incisor; for which a poor prognosis was considered following an endodontic treatment. There was a history of sudden facial swelling during root canal therapy. With the exacerbation of the problem and experiencing other symptoms, she was hospitalised. CT scan showed bilateral extension and penetration of air into submandibular, peri-orbital and parapharyngeal spaces. Clinical and radiographic evaluations of the maxillary lateral incisor revealed mid-root perforation on its buccal side, which was sealed by MTA. Eventually, the tooth was successfully restored. Keywords: Necrotizing Fasciitis; Root Perforation; Subcutaneous Emphysema